Association between heart rate variability indices and features of spontaneous ventricular tachyarrhythmias in mice. (28th February 2020) - He, Mi; Zhao, Wei‐Bo; Nguyen, My‐Nhan; Kiriazis, Helen; Li, Yong‐Qin; Hu, Houyuan; Du, Xiao‐Jun
Abstract: Direct evidence is limited for the association between heart rate variability (HRV) indices and ventricular tachyarrhythmias (VTAs). While galectin‐3 (Gal‐3) is regarded as a causal factor for cardiac remodelling and a biomarker for arrhythmias, its regulation on VTAs and HVR is unknown. Using aged transgenic (TG) mice with cardiac overexpression of β 2 ‐adrenoceptors and spontaneous VTAs, we studied whether changes in HRV indices correlated with the severity of VTAs, and whether Gal‐3 gene knockout (KO) in TG mice might limit VTA. Body‐surface ECG was recorded (10‐minute period) in 9‐ to 10‐month‐old mice of non‐transgenic (nTG), TG and TG × Gal‐3 knockout (TG/KO). Time‐domain, frequency‐domain and nonlinear‐domain HRV indices were calculated using the R‐R intervals extracted from ECG signals and compared with frequency of VTAs. TG and TG/KO mice developed frequent VTAs and showed significant changes in certain time‐domain and nonlinear‐domain HRV indices relative to nTG mice. The severity of VTAs in TG and TG/KO mice in combination, estimated by VTA counts and arrhythmia score, was significantly correlated with certain time‐domain and nonlinear‐domain HRV indices. In conclusion, significant changes in HRV indices were evident and correlated with the severity of spontaneous VTAs in TG mice. The frequency of VTA and HRV indices were largely comparable between TG and TG/KO mice. Deletion of Gal‐3 in TG mice altered certain HRV indices implying influence by neuronally localized Gal‐3 on autonomic nervous activity.